WANITA PENYAIR DALAM PETA KESUSTRAAN INDONESIA - Saraswati, Ekarini (Jurnal Bestari, 1992)
Poem is one of ways that poets express their deep emotions. Poets or poetesses thorugh poem are able to critisize the bad moral of a certain society. A poem, moreover, can improve young generation's behaviour. In Indonesia, the total of poetesses ae fewer than poets. The literature world, however, usually emphasizes the quality of master piece and ignore the amount of writers.